Упрочнение поверхностного слоя наплавленных деталей при точении резцами с ПКНБ «Киборит» - Коломиец, Владимир Алексеевич; Ридный, Р.; Никифоров, А. В.; Клименко, С. (Національний технічний університет "Харківський політехнічний інститут", 2020)
Приведены результаты экспериментального исследования упрочнения поверхностного слоя наплавленных деталей при механической обработке резцами, оснащенними поликристаллическим сверхтвердым материалом на основе кубического нитрида бора «киборит». Использовались резцы с большой величиной переднего угла. Изучено влияние режимов обработки на величину поверхностной микротвердости и толщину упрочненного поверхностного слоя деталей. Показана возможность увеличения микротвердости поверхностного слоя наплавленных деталей в 1,8–2,1 раза.

The results of an experimental study of hardening of the surface layer of parts deposited by electric arc welding with Np-30KhGSA wire under a flux layer of AN-348A are presented, when machined with cutters equipped with replaceable non-milling plates RNMN 070300 made of polycrystalline superhard material (PCBN) based on cubic boron nitride «ciborite». The influence of mining regimes on the surface microhardness and the thickness of the hardened surface layer of parts is studied. The nature of the lines of equal microhardness indicates a less significant effect of the cutting speed compared to the depth of cut and feed and a close degree of influence of changes in the latter. Processing speeds have less effect on the thickness of the hardened layer compared to the depth of cut and the amount of feed, although the latter has a less intense effect. The greatest hardening of the deposited parts was achieved by turning with a cutter with rake angles of (40–50)°. Treatment with chisels with PCBN «ciborite» with large negative values of the front angle γ is accompanied by the creation in the processing area of such a level of thermobaric load, which leads to structural changes in the surface layer of parts, namely, a layer of weakly etchable hardening structure – unstructured martensite H50 = 5700–5920 MPa, which is 1.8–2.1 times higher than the microhardness of the main weld material. The thickness of the reinforced deposited layer during blade-hardening processing with a tool with PCBN «ciborite» is 60–80 μm, due to the low carbon content in the material, the presence of ascending diffusion of carbon and intense plastic deformation in the contact zone. The results show that blade-hardening machining with tools with PCBN is an effective method of controlling the performance of machine parts, such as their wear resistance.
Strengthening of the surface layer of the weld parts when turning by cutters with PSTM “Kiborit”
Keywords: инструмент с ПСТМ; микротвердость; толщина упрочненного слоя; tool with PCBN «cibоrite»; hardened surface layer; microhardness